Upaya meningkatkan keterampilan motorik kasar anak kelompok b melalui permainan dengan simpai di taman kanak-kanak - Lastuti Utami (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This study aims to improve the gross motor skills of group B2 children through games with hoops in Pertiwi Sengi 2 Kindergarten, Dukun District, Magelang Regency, 2019/2020 academic year. This research is a Classroom Action Research (PTK), which was carried out because the gross motor skills of group B children in TK Pertiwi Sengi 2 experienced obstacles if they did not use tools or media to stimulate their development. This classroom action research method uses three cycles, each of which is carried out for six days. While the results to be achieved in this CAR are: 1) Increasing children's gross motor skills after playing games with hoops. 2) increasing the sense of cooperation between children or children. 3) children are able to control their emotions. 4) children are able to move their limbs quickly, especially their hands and feet. 5) the child has a positive desire to compete. 6) children want to acknowledge the superiority of their friends or other groups. Thus at the same time training children to accept their defeat without feeling angry or disappointed. So with this CAR, the expected results are not only physical development, but also emotional development and also children's character education